The Frequency of SMN1, SMN2 Copy Numbers in 246 Turkish Cases Analyzed with MLPA Method - Yalcintepe, Sinem; Karal, Yasemin; Demir, Selma; Atli, Emine Ikbal; Atli, Engin; Eker, Damla; Mail, Cisem; Zhuri, Drenushe; Guler, Hazal Sezginer; Gurkan, Hakan (Global Medical Genetics, 2023)
This study aimed to define the copy numbers of SMN1 and SMN2 genes and the diagnosis rate and carrier frequency of spinal muscular atrophy (SMA) in the Thrace region of Turkey. In this study, the frequency of deletions in exons 7 and 8 in the SMN1 gene and SMN2 copy numbers were investigated. A total of 133 cases with the preliminary diagnosis of SMA and 113 cases with the suspicion of being an SMA carrier from independent families were analyzed by multiplex ligation-dependent probe amplification method for SMN1 and SMN2 gene copy numbers.SMN1 homozygous deletions were detected in 34 patients (25.5%) of 133 cases with the suspicion of SMA. Cases diagnosed with SMA type I was 41.17% (14/34), 29.4% (10/34) with type II, 26.4% (9/34) with type III, and 2.94% (1/34) with type IV. The SMA carrier rate was 46.01% in 113 cases. In 34 SMA cases, SMN2 copy numbers were: two copies – 28 cases (82.3%), three copies – 6 cases (17.6%). SMN2 homozygous deletions were detected in 15% (17/113) of carrier analysis cases. The consanguinity rate of the parents was 23.5% in SMA diagnosed cases. In this study, we had a 25.5% of SMA diagnosis rate and 46% SMA carrier frequency. The current study also showed the relatively low consanguinity rate of the Thrace region, with 23.5% according to the east of Turkey.
Keywords: spinal muscular atrophy; SMN1; SMN2; copy number; consanguinity